PSYCHOMOTRICITY AND CHILDREN WITH AUTISM SPECTRUM DISORDER (ASD) (Fiep Bulletin - online, 2025)
Introduction: Psychomotricity is an approach that integrates motor, emotional and cognitive aspects, playing an essential role in the development of children with Autism Spectrum Disorder (ASD). Physical Education promotes the improvement of motor coordination, balance and body perception, favoring the autonomy and socialization of these students. Objective: The objective of this study was to present how psychomotricity acts in the development of children with Autism Spectrum Disorder (ASD). Methods: The methodology is a systematic review of the literature, carried out in the VHL, ERIC and Google Scholar databases, referring to the period between 2019-2024. Results: The search process resulted in 354 findings. After the screening processes, six studies were selected that met the research requirements. Conclusion: It was concluded that psychomotricity should be treated as an effective approach in the development of children with ASD, promoting improvements in the motor, social and cognitive domains. However, future research must address current limitations to establish more robust intervention protocols and understand the long-term effects of these strategies.
Keywords: Psychomotricity; Physical Education; Autism Spectrum Disorder; children